Pembuatan Film Pendek IT In Millennial Daily Life dengan Teknik Handheld dan Continuity Cutting - Dela Harum Novia Sari; Herocyma; Septira Kurniati; Ahmad Chusyairi (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Making a work through a short film is a pride to make a better experience for thefuture. With the short film can put wisdom or a lesson in it and draw the attention ofthe audience to learn to make short films, for hobbies and to work in the field ofvideography. In making a short film, it certainly requires technical requirements init. So that people who see, make and understand the contents in the short film so theycan know the techniques used. One of them is to make a short film entitled IT inMillennial Daily Life by using handheld techniques and continuity cutting in it. Theexistence of making a short film with the title IT in Millennial Daily Life, has theaim to provide information that today many people who in their daily lives are verydependent on technology. The use of technology that can be done anytime andanywhere or commonly called IT for life. In making the short film, using the twotechniques already mentioned, namely the handheld technique and continuitycutting, which aims to produce videos that do not shake or shake, and the continuitycutting technique in the video editing process produces a video transfer that is nottoo flashy. This film was made to channel a hobby in videography by taking part inthe INDOCORIS COMPETITION 2019 Short Movies category